Impact of Lung Boost Exerciser on Inspiratory Muscle Strength post Abdominal Surgeries - Elzoghpy, Shrouk M. Mahrous; Abdelhameed, Marwa M.; Raslan, Mohamed M.; Hussain, Ghada S.; Abdelrashid, Nessrien A. (Journal of Neonatal Surgery, 2025)
Background: Abdominal surgery often leads to the occurrence of postoperative pulmonary complications (PPCs). Reduced maximum inspiratory volumes, an inability to overcome postoperative atelectasis, and a higher risk of developing a PPC result from weaker respiratory muscles' reduced capacity to produce enough effort to expand non-compliant lung tissue Purpose: This study was done to evaluate the effect of lung boost exerciser on inspiratory muscle strength post upper abdominal surgeries Materials and methods: sixty patients of post upper abdominal surgeries both sex patients, aged from 35-50 years old, were randomly allocated from KasrEliny Hospital, throughout the period between July and February 2024/2025, patients were randomized into two groups (Experimental group(A) and Control group(B)), the treatment lasted four weeks , the assessments were performed on the selected patients three times; pretreatment , two weeks post treatment then four weeks post treatment. Maximum inspiratory pressure (MIP)was assessed using Respiratory pressure check, measuring inspiratory muscle strength. Result: a significant increase was noted in the maximum inspiratory pressure (MIP) of group A compared to that of group B at post I (d = 1.03, p < 0.001) and post II (d = 1.95, p < 0.001). Conclusion: Adding lung boost exerciser to conventional chest physiotherapy has favorable outcomes for patients having upper abdominal surgeries